Advogados e trabalhadores perante a justiça do trabalho: forma de atuação, limites e possibilidades na ditadura do Estado Novo em Santa Maria - RS (1937-1945) - Pompéo, Wagner Augusto Hundertmarck (2021)
Despite the significant increase in the volume and quality of research produced in the field of the social history of labour, with records of greater openness in terms of themes and approaches, it is found that, especially regarding the period of the Estado Novo (1937-1945), they could not explain the role played by labor lawyers in the then new Labour Justice. In that regard, this PhD thesis aims to (re)construct the history of these professionals and their legal work – form of action, limits and possibilities – throughout this period of political and cultural domination in which, marked by a strong discourse of giving and protection of labour rights, the State sought the control of workers. For such, we will analyse consistent primary sources in historical labour processes currently crowded in the collection of Santa Maria’s Labour Justice Memorial, through which, in addition to having been able to draw a profile of the plaintiffs, types of demands and discussions more commonly found, we also identified the professionals of the law who most commonly defended the employees and employers of the municipality. Professionals who, as indicated in the conclusions reached, were at the epicentre of the first discussions about (dis)compliance and (in)effectiveness of the newly established social legislation of the time, a fact that made them as important as the employees, employers and Judges themselves, given their fundamental role and contributed to the gradual construction and maturation of the social legislation of the time.